Evaluation of flexural strength and antibacterial effect of orthodontic acrylic resins containing Galla chinensis extract - Shabnam Ajami; Raha Habibagahi; Reza Khashei; Malihe Soroorian (Dental Press Journal of Orthodontics, 2021)
ABSTRACT Objective: To evaluate different concentrations of Galla chinensis extract (GCE) added to poly(methyl methacrylate) (PMMA), which is widely used for fabrication of removable orthodontic appliances, regarding the effectiveness of this herbal extract on antimicrobial effect and flexural strength of PMMA. Methods: Acrylic resin samples containing 0.4%, 0.8% and 1.6% GCE were prepared. Flexural strength was investigated via three-point flexural strength test for the 15 acrylic resin blocks of each concentration. Disk diffusion test was used to evaluate antibacterial effects of incorporating the same concentrations of GCE into acrylic resin. All these three groups were compared with the control group, with no added GCE, regarding flexural strength and antibacterial properties. Results: Comparison of flexural strength between the three study groups and the control group showed significant differences between the groups (P=0.018). However, there was no significant difference between the groups containing GCE. There were significant differences in antimicrobial activity between the four groups (P=0.026). Conclusion: Within the limitations of this study, it is suggested that incorporation of GCE into PMMA would be beneficial for antimicrobial activity and flexural strength of PMMA, but further studies on other physical properties and antimicrobial effects on other bacterial strain would be beneficial prior to clinical investigations.